2011
DOI: 10.3109/1547691x.2010.546382
|View full text |Cite
|
Sign up to set email alerts
|

Lung exposure of titanium dioxide nanoparticles induces innate immune activation and long-lasting lymphocyte response in the Dark Agouti rat

Abstract: Nanomaterial of titanium dioxide (TiO2) is manufactured in large-scale production plants, resulting in risks for accidental high exposures of humans. Inhalation of metal oxide nanoparticles in high doses may lead to both acute and long-standing adverse effects. By using the Dark Agouti (DA) rat, a strain disposed to develop chronic inflammation following exposure to immunoactivating adjuvants, we investigated local and systemic inflammatory responses after lung exposure of nanosized TiO2 particles up to 90 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 43 publications
7
49
0
Order By: Relevance
“…We also demonstrated an increase of eosinophils in NS mice exposed to SiO 2 NPs, a phenomenon also observed in rats after titanium NP exposure. 10 The observation that, 24 hours after intratracheal instil lation, the percentage of FITC + cells in S mice was higher compared to NS mice, is in agreement with our earlier study. 28 NP uptake occurred mainly by pulmonary macrophages, as has been observed in healthy animals.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…We also demonstrated an increase of eosinophils in NS mice exposed to SiO 2 NPs, a phenomenon also observed in rats after titanium NP exposure. 10 The observation that, 24 hours after intratracheal instil lation, the percentage of FITC + cells in S mice was higher compared to NS mice, is in agreement with our earlier study. 28 NP uptake occurred mainly by pulmonary macrophages, as has been observed in healthy animals.…”
supporting
confidence: 82%
“…the circulatory and lymphatic systems, causing longlasting cell damage. 10,11 Several studies show that SiO 2 NPs induce dosedependent cytotoxicity in in vitro systems, including human lung epithelial cells 12 and bronchoalveolar carcino maderived cells 13 and human alveolar barrier, 14 as well as murine macrophages. 15 Shortterm instillations or inhalation exposure to amorphous SiO 2 NPs showed that these particles possess the potential to cause toxic effects in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in total cell counts in BALF may affect the influx of not only macrophages but also neutrophils, and that is not sufficient to reflect the neutrophil inflammation. There are reports that the proinflammatory cytokines interleukin-1 (IL-1), IL-6 and tumor necrosis factor (TNF) were upregulated in the acute period in animal models exposed to inhaled crystalline silica and TiO 2 [33][34][35]. These transient upregulations of proinflammaory cytokines may play a key role in sustained pulmonary inflammation, but changes in proinflammatory cytokines may not sufficiently reflect the pulmonary toxicity of nanomaterials due to the short response period, and may not be useful as predictive markers of the pulmonary toxicity of nanomaterials.…”
Section: Endpointsmentioning
confidence: 99%
“…The risk of being exposed to NPs is particularly high for those working with the production of engineered NPs (European Union, SWD (2012) 288 final). Recently, it has been shown that exposure to engineered NPs can induce airway inflammation in animals (Gustafsson et al, 2011;Rossi et al, 2010;Roursgaard et al, 2011), induce adverse health effects in sensitized mice during the development of eosinophilic airway inflammation (Jonasson et al, 2013), and also induce lung tissue fibrosis in mice (Ryman-Rasmussen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%